A cross-national analysis of the guarantees of rights. Issue 4 (September 2014) - Sommer, Udi; Asal, Victor
What are the predictors of rights guarantees at the level of individual countries? We examine this question within the context of what factors lead certain countries, but not others, to have legislation prohibiting sexual orientation discrimination in the workplace between 1972 and 2002. In the theoretical framework, a combination of domestic forces (past inclusion of minorities, culture, and democratic conditions) and global trends (regulation by supranational bodies and globalization) predict guarantees of rights. To test the theory, generalized estimating equation time-series cross-sectional analyses are performed on data from 161 countries. The results, which are robust to changes in model specification and alternative measurement schemes, confirm our key hypotheses. We conclude by discussing the implications of this research for the study of rights generally.